Pengaruh Komunikasi, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Pada Karyawan RSUD Namlea Kab.Buru Provinsi Maluku) - Rasman Buton; Abdul Kodir Djaelani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine the effect of communication, work motivation and work environment on employee performance in Namlea Hospital. The sample in this study amounted to 46 respondents. The data analysis technique used multiple linear regression.The results of descriptive analysis in this study indicate that the employees of the Namlea Hospital perceive all research, namely communication, work motivation, work environment, and employee performance. Communication has a significant effect on the performance of the Namlea Hospital employees. Work motivation has a significant effect on the employee performance of Namlea Hospital. The work environment has a significant effect on the Employee Performance of Namlea Hospital. Communication, work motivation, and work environment simultaneously influence the performance of the Namlea Hospital employees Keywords: Communication, Work Motivation, Work Environment, and Employee Performance